2016
DOI: 10.1016/j.amc.2015.07.071
|View full text |Cite
|
Sign up to set email alerts
|

The PCHIP subdivision scheme

Abstract: In this paper we propose and analyze a nonlinear subdivision scheme based on the monotononicitypreserving third order Hermite-type interpolatory technique implemented in the PCHIP package in Matlab. We prove the convergence and the stability of the PCHIP nonlinear subdivision process by employing a novel technique based on the study of the generalized Jacobian of the first difference scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…In what follows, we set the notation for the remainder of the paper and briefly review those tools used in the analysis of stationary subdivision schemes (linear or not) that are relevant in our development. The interested reader is referred to [4,12] for a more complete description of the theory of linear subdivision schemes, and to [2,3,8,9,16] for the relevant theory of nonlinear subdivision schemes that can be written as a nonlinear perturbation of a convergent linear scheme. In the following we use the letter T only for linear schemes, while S shall denote a general subdivision scheme (linear or not).…”
Section: Convergence Of Stationary Subdivision Schemesmentioning
confidence: 99%
See 2 more Smart Citations
“…In what follows, we set the notation for the remainder of the paper and briefly review those tools used in the analysis of stationary subdivision schemes (linear or not) that are relevant in our development. The interested reader is referred to [4,12] for a more complete description of the theory of linear subdivision schemes, and to [2,3,8,9,16] for the relevant theory of nonlinear subdivision schemes that can be written as a nonlinear perturbation of a convergent linear scheme. In the following we use the letter T only for linear schemes, while S shall denote a general subdivision scheme (linear or not).…”
Section: Convergence Of Stationary Subdivision Schemesmentioning
confidence: 99%
“…Then, convergence can be proven using the following result from [3] (notice the similarity with (9)).…”
Section: Convergence Of Stationary Subdivision Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pchip stands for piecewise cubic hermite interpolating polynomial, which is an interpolation method in which a cubic polynomial approximation is assumed over each subinterval. Aràndiga et al (2016) describe this interpolation scheme in detail together with its advantages, mainly that it is both accurate (preserves values at the nodes) and preserves monotonicity. Pchip was selected for the present study because (i) the fitted curve passes through observed values at inflexion points unlike spline or quadratic methods, for example, and (ii) it does not require re-fitting when the period of application is extended as each subinterval is treated separately.…”
Section: Temperature Datamentioning
confidence: 99%
“…Nonlinear subdivision schemes like ENO, WENO, PPH and PCHIP [1][2][3][4][5][6][7][8][9], were introduced during last several years to address Gibbs phenomenon. The arithmetic mean of second differences was replaced by their harmonic mean in a linear subdivision scheme to change it to a nonlinear scheme in [1,2].…”
Section: Introductionmentioning
confidence: 99%